2013
DOI: 10.3389/fneur.2013.00082
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Associated Disease in a Neurointensive Care Unit

Abstract: Background: Critically ill patients are at high risk for acquiring Clostridium difficile infection. The aim of this study was to investigate the prevalence, severity, and outcome of neurointensive care unit (NICU) acquired Clostridium difficile associated disease (CDAD).Materials and Methods: Intensive care admission and hospital infection control databases from April 2008 to August 2010 were studied and the case notes reviewed retrospectively. Diarrhea was classified as mild, moderate, or severe based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Among the 80 835 ICU patients in our analysis, the pooled prevalence of CDI was 2% (95% CI, 1%–2%; τ 2 = 0.01) (Figure 2 ), with no evidence of small study effects across studies (Egger's bias 1.53, P = .142). The prevalence of CDI across North America studies was 2% [95% CI (1%–4%), τ 2 = 0.02] [ 17 , 18 , 20 22 , 24 , 25 , 28 ], whereas the estimated prevalence across Europe was 1% (95% CI, 1%–2%; τ 2 = 0.01) [ 13 16 , 19 , 23 , 27 , 29 32 , 34 ] and the estimated prevalence across Asia was 3% (95% CI, 1%–2%; τ 2 = 0.01) [ 26 , 33 ]. Among 3621 diarrheic ICU patients, the pooled prevalence of CDI was 11% (95% CI, 6%–17%; τ 2 = 0.08), with no small study effect (Egger's bias 1.01, P = .156) [ 14 , 18 , 19 , 25 – 27 , 29 – 31 , 33 , 34 ] ( Supplementary Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 80 835 ICU patients in our analysis, the pooled prevalence of CDI was 2% (95% CI, 1%–2%; τ 2 = 0.01) (Figure 2 ), with no evidence of small study effects across studies (Egger's bias 1.53, P = .142). The prevalence of CDI across North America studies was 2% [95% CI (1%–4%), τ 2 = 0.02] [ 17 , 18 , 20 22 , 24 , 25 , 28 ], whereas the estimated prevalence across Europe was 1% (95% CI, 1%–2%; τ 2 = 0.01) [ 13 16 , 19 , 23 , 27 , 29 32 , 34 ] and the estimated prevalence across Asia was 3% (95% CI, 1%–2%; τ 2 = 0.01) [ 26 , 33 ]. Among 3621 diarrheic ICU patients, the pooled prevalence of CDI was 11% (95% CI, 6%–17%; τ 2 = 0.08), with no small study effect (Egger's bias 1.01, P = .156) [ 14 , 18 , 19 , 25 – 27 , 29 – 31 , 33 , 34 ] ( Supplementary Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on 4 studies [ 26 , 27 , 32 , 34 ], we found that 25% (95% CI, 5%–51%; τ 2 = 0.17) of ICU patients with confirmed CDI had pseudomembranous colitis determined either with imaging or endoscopic findings [ 26 , 27 , 32 , 34 ] ( Supplementary Figure 4 ). It is worth noting that we excluded from this calculation the study by Buendgens et al [ 15 ], where only patients with pseudomembranous colitis were deemed to have CDI, in an effort to avoid overestimating the result.…”
Section: Resultsmentioning
confidence: 99%
“…The reported incidence of CDI in the ICUs of North America and Europe was 8.7–53.9 cases per 10,000 patient-days [ 8 12 ], or 0.4–4% of the ICU population [ 12 17 ]. A recent meta-analysis revealed a global CDI incidence rate of 2% among critically ill patients [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of CDI in patients admitted to the ICU is scarce and usually refers to short periods and patients who have acquired CDI during their ICU stay; it omits CDI episodes occurring before admission or even during the first 24 to 72 hours of admission [7][8][9][10]19,[23][24][25]. We put this issue into perspective: the percentage of A-ICU CDI cases acquired before ICU admission was 16.2%; in the few studies addressing this matter, results range from 17.4% to 47% [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%